Isolation of lesbian, gay, bisexual and transgender youth: a dimensional concept analysis. (22nd July 2013) - Johnson, Michael J.; Amella, Elaine J.
Abstract Aim To present the findings of a dimensional analysis of isolation in the context, and from the perspective, of lesbian, gay, bisexual and transgender youth. Background Lesbian, gay, bisexual and transgender youth are often at greater risk for negative health outcomes compared with heterosexual youth. Isolation is one risk factor cited throughout the literature; however, the concept is complicated and has many uses and thus warrants clarification. Design Concept Analysis. Data Sources Sources comprise 35 English language research articles retrieved from CINAHL and EBSCOHost (1987–2012). Methods A dimensional concept analysis was undertaken to analyse how the concept, isolation, is socially constructed. Results This dimensional analysis revealed five socially constructed dimensions and four sub‐dimensions. These findings indicate that there is substantial variability in the concept of isolation. These differences and variations are most notably observed in the 20 articles (57%) that had more than one dimension. Although some of these articles were explicit with the different meanings and use of the concept, most of the papers had wide variability in the use and meaning of the concept. Conclusion The disproportionately greater physical and mental health disparities between lesbian, gay, bisexual and transgender and heterosexual youth are a signal to conduct more research to clarify the concept of isolation, to develop instrumentation to identify at‐risk youth and to explore predictors and consequences of isolation. Nurses and others can lead the way in translating this knowledge into strategies that will improve the health and lives of these young people.